Recouping the costs of apprenticeship training: employer case study evidence from England - Gambin, Lynn [Verfasser]; Hasluck, Chris [Verfasser]; Hogarth, Terence [Verfasser] (My University, 2010)
"From a public policy perspective where the aim is to increase the number of employers providing Apprenticeships in a system which provides policy makers with few demand side levers the most persuasive argument policy makers can craft is one based on demonstrating that investing in Apprenticeships will yield a positive return to the employer. This paper outlines a method for calculating the return to the employer and, based on a series of in-depth employer case studies conducted in England during 2007/8, provides estimates of how quickly employers in different sectors of the economy can recoup their investments in Apprenticeships." (Autorenreferat, BIBB-Doku)
Keywords: S 1.3 Berufliche Erstausbildung; S 4.3.3 Effizienz & Effektivität des Berufsbildungswesens; S 4.3.6 Human Capital; I 2.2.1 Westeuropa; Betriebliche Berufsausbildung; Kosten-Nutzen-Analyse; Humankapital; Bildungsertrag; Wirtschaftszweig; Fallstudie; England